To thrive or not to thrive: Pathways for sustaining thriving at work. (February 2022) - Porath, Christine L.; Gibson, Cristina B.; Spreitzer, Gretchen M.
Abstract: Thriving, the psychological experience of both vitality (or energy) and learning, is often elusive. Rather than growing, developing, and feeling energized, workers report stagnation and depletion. While much of the research on thriving at work has focused on what managers can do to promote thriving amongst workers, we highlight the means by which people are empowered to take control of their well-being. Workers can sustain their own thriving through three pathways: (1) by engaging in self-care, (2) creating and maintaining high quality relationships, and (3) building community within and outside the organization. We show that these three pathways are particularly important given the changing nature of more temporary and flexible work arrangements, increases in remote work, and the larger need for community embeddedness to address the many grand societal challenges that confront us.